Comparison of Wound Complications Between Two Closing Techniques Following Total Hip Arthroplasty Via the Direct Anterior Approach - Opanova, Maria; Hasegawa, Ian; Unebasami, Emily; Tollefsen, Cera-Nicole; Saito, Sean; Andrews, Samantha; Nakasone, Cass (The Journal of Hip Surgery, 2019)
A higher rate of wound complications has been reported in the direct anterior approach (DAA) for total hip arthroplasty (THA), reportedly due to the location of the incision and poor surgical site exposure techniques. Therefore, the purpose of this study was to compare wound complications within the first 90 days between a zipper closing method (ZM) and subcuticular monocryl with dermabond skin closure (SMD). A total of 294 patients (352 hips) were closed using the SMD and 166 patients (206 hips) were closed via the ZM. All THAs via the DAA and postoperative care were performed based on the current standard of care for the treatment of symptomatic hip osteoarthritis, established by a single, high volume surgeon from 2016 to 2018. Any wound complications during the first 90 days were noted. Independent t-tests determined differences in descriptive variables. Additionally, a Fisher Exact test was performed to compare wound complication rate between groups (p < 0.05). Surgical time was significantly shorter for ZM (p < 0.001) for both unilateral and bilateral groups compared with SMD. Overall, there were four complications occurring in 558 cases (0.7%), with two cases (0.36%) requiring additional surgery. No wound complications were present in the SMD and four wound complications (1.9%), two requiring surgery, were reported for the ZM (χ2 [1, N = 558] = 6.884, p = 0.009). While no wound complications were reported in the SMD group, the ZM group sustained four wound complications, two of which required additional surgery. Two of these wound complications occurred within the first 14 cases following implementation of the ZM, perhaps indicating a short learning curve. The ZM is a quicker, perhaps easier closure method yet the added expense for materials and suggested increased risk for wound complications may moderate the enthusiasm of the ZM compared with the sutures following THA via the DAA.
Keywords: direct anterior approach; total hip arthroplasty; wound closure; Zipper method; sutures